Deteksi Cucumber Mosaic Virus (CMV) dan Chili Veinal Mottle Virus (ChiVMV) pada Gulma Commelina spp. di Pertanaman Cabai(Capsicum spp.) Melalui Teknik Uji Serologi dan Molekuler - VENIARI, NI KADEK; YULIADHI, KETUT AYU; NYANA, I DEWA NYOMAN; SUASTIKA, GEDE (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2015)
ABSTRACT Detection of Cucumber Mosaic Virus( CMV ) and Chilli Veinal Mottle Virus ( ChiVMV) on Weed Commelina spp. In Cropping Chilli Pepper( Capsicum spp .) Through Serology and Molecular Test This study aims to determine the type of weed Commelina spp. which became an alternative host Cucumber mosaic virus (CMV) and Chili veinal mottle virus (ChiVMV) in pepper, as well as the detection of CMV and ChiVMV which infects the weed Commelina spp. use molecular methods. DAS-ELISA ( Double Antibody Sandwich-Enzyme Link ed Immunosorbent Assay ) and molecular techniques through RT-PCR (Reverse Transcription-Polymerase Chain Reaction) are used. Research activities include (1) Survey mosaic symptoms and disease incidence in the field; (2) Identification the type of weed that grows on pepper plants area; (3) Preservation of samples Commelina spp. weed and chili which virussymptomatic; (4) Test through DAS-ELISA serology; (5) Molecular detection by RT-PCR. The research proves that the weed Commelina spp . can be alternate hosts ChiVMV and CMV, also CMV and ChiVMV can infect weedsCommelina spp in chilicropping. DAS-ELISA test results show samples of the weed Commelina spp . and chili infected with Cucumber mosaic virus (CMV) and Chili veinal mottle virus (ChiVMV). RT-PCR technique successfully applying DNA target fragment size of 657 bp and 900 bp for CMV and ChiVMV accordance with the specific primers used.   Keyword : Chili pepper , CMV , ChiVMV , weeds com m elina
Keywords: chili pepper; CMV; ChiVMV; weeds commelina